2015
DOI: 10.5897/err2015.2306
|View full text |Cite
|
Sign up to set email alerts
|

Metasynthesis of in-service professional development research: Features associated with positive educator and student outcomes

Abstract: Findings from a metasynthesis of 15 research reviews of in service professional development to improve or change teacher content knowledge and practice and student/child knowledge and behavior are described. The research reviews included 550 studies of more than 50,000 early intervention, preschool, elementary, and secondary education teachers, educators, and practitioners. The goal of metasynthesis is to identify the common and core features of in service professional development associated with changes and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…The particular approach to coaching used by the practitioners included the methods and procedures for (1) introducing and illustrating the practices to the parents, (2) engaging the parents in the use of the practices and their self-evaluation of their experiences, (3) the procedures used by the practitioners to facilitate parents' reflection on and understanding of the key characteristics of the practices, and (4) the procedures used to sustain parents' use of the interest-based language learning practices. This set of strategies was used by the practitioners as an evidence-based implementation practice to promote parents' adoption and use of the intervention practices with their children (Dunst, Bruder, & Hamby, 2015; .…”
Section: Learning Practicesmentioning
confidence: 99%
“…The particular approach to coaching used by the practitioners included the methods and procedures for (1) introducing and illustrating the practices to the parents, (2) engaging the parents in the use of the practices and their self-evaluation of their experiences, (3) the procedures used by the practitioners to facilitate parents' reflection on and understanding of the key characteristics of the practices, and (4) the procedures used to sustain parents' use of the interest-based language learning practices. This set of strategies was used by the practitioners as an evidence-based implementation practice to promote parents' adoption and use of the intervention practices with their children (Dunst, Bruder, & Hamby, 2015; .…”
Section: Learning Practicesmentioning
confidence: 99%
“…Capacity-building professional development is defined as the experiences and opportunities used by professional development specialists to engage learners (e.g., early childhood intervention practitioners) in activities to improve their knowledge, skills, and intervention practices (Desimone, 2009;Guskey, 2002). Evidence-based professional development is defined as practices informed by research findings demonstrating an empirical relationship between particular types of adult learning and professional development practices and learner outcomes (Dunst, Bruder, & Hamby, 2015;Dunst, Trivette, & Hamby, 2010). Findings from a meta-analysis of adult learning studies, for example, indicated that coaching over extended periods of time "stood out" as an especially important element of evidence-based professional development .…”
Section: Introductionmentioning
confidence: 99%
“…These included explicit efforts to establish the credibility of the TA provider and the proposed approach to TA; the use of some type of professional development or training to promote staff abilities to use targeted practices; the use of coaching or mentoring by the TA provider as part of professional development; TA provider consultation in response to staff requests for assistance and guidance; and TA provider supports and performance feedback in response to progress toward using targeted intervention practices. Although nearly all TA model and framework developers noted the importance of TA provider professional development, there was very little consensus in terms of the types of professional development that should be used, and not a single model or framework included a description of or reference to evidence-based adult learning or professional development (Dunst, Bruder, & Hamby, 2015;Dunst, Trivette, & Hamby, 2010) as important for capacity-building purposes.…”
Section: Provision Of Technical Assistancementioning
confidence: 99%